Hypervalent Iodine(III) in Direct Carbon–Hydrogen Bond Functionalization - Narayan, Rishikesh; Manna, Srimanta; Antonchick, Andrey P. (Synlett, 2015)
Direct methods of novel bond formation through functionalization of nonreactive carbon–hydrogen bonds represent an efficient synthetic approach. Cross-dehydrogenative coupling has emerged as an area of huge potential and importance for novel bond formation. The application of hypervalent iodine(III) reagents in direct carbon–hydrogen bond functionalization reactions is of immense interest because the functionalization of the nonreactive carbon–hydrogen bonds proceeds under metal-free reaction conditions. This account covers recent developments in the area of hypervalent iodine(III) mediated direct carbon–hydrogen bond functionalization.1 Introduction2 Intramolecular Amination for Carbazole Synthesis3 Intermolecular Amination4 Intermolecular Annulation5 Intermolecular Nucleophilic Amination6 Hypervalent Iodine(III) Mediated Radical Reactions6.1 Cross-Dehydrogenative Coupling of a Heterocycle and an Aldehyde6.2 Cross-Dehydrogenative Coupling of a Heterocycle and an Alkane6.3 Intramolecular Cyclization7 Conclusion
Keywords: hypervalent iodine; aminations; heterocycles; organocatalysis; cross-dehydrogenative coupling